2015
DOI: 10.1111/cxo.12263
|View full text |Cite
|
Sign up to set email alerts
|

Stretch‐dependent changes in surface profiles of the human crystalline lens during accommodation: A finite element study

Abstract: Background A nonlinear isotropic finite element (FE) model of a 29 year old human crystalline lens was constructed to study the effects of various geometrical parameters on lens accommodation. Methods The model simulates dis-accommodation by stretching of the lens and predicts the change in the lens capsule, cortex and nucleus surface profiles at select states of stretching/accommodation. Multiple regression analysis (MRA) is used to develop a stretch-dependent mathematical model relating the lens sagittal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Contrary to the results reported by Fisher [7], Wilde et al [10] showed that the lens nucleus becomes stiffer than the lens cortex around the fourth to fifth decade of life. The present study adopts a similar modelling concept as in several previous studies [36][37][38][39] by constructing axisymmetric lens models, each with three different sections of zonular fibres. Each developed model was constructed in accordance with geometries of an intact lens rather than an assemblage of parameters from various sources [36,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to the results reported by Fisher [7], Wilde et al [10] showed that the lens nucleus becomes stiffer than the lens cortex around the fourth to fifth decade of life. The present study adopts a similar modelling concept as in several previous studies [36][37][38][39] by constructing axisymmetric lens models, each with three different sections of zonular fibres. Each developed model was constructed in accordance with geometries of an intact lens rather than an assemblage of parameters from various sources [36,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The present study adopts a similar modelling concept as in several previous studies [36][37][38][39] by constructing axisymmetric lens models, each with three different sections of zonular fibres. Each developed model was constructed in accordance with geometries of an intact lens rather than an assemblage of parameters from various sources [36,38,39]. In addition, a nodal coupling mechanism was introduced to anchorage points of zonular fibres on the lens capsule, to maintain smooth curvatures at the lens periphery during simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior, equatorial and posterior sections of the zonule originate from different locations on the ciliary body [4]. Yet a number of modelling approaches simplify these forces as emanating from a single point [5], [6], [7], [8], [9]. Recently it was shown that separating directions of zonular force across the three sections makes a substantial difference to the shape change and renders the modelled simulation closer to the changes in shape seen in the biological lens [10].…”
mentioning
confidence: 99%
“…Almost all previous modelling studies assumed uniform distributions of material properties in the lens nucleus and cortex, and used lens models based on limited ages [5], [6], [7], [8], [9]. This study describes advanced models that correlate distributions of material properties derived from in vitro optical measurements of refractive index [23] with in vivo mechanical analyses [22].…”
mentioning
confidence: 99%